Adoption of ICT by sheep farmers in the Western Cape (Karoo and Eden): towards sustainable farming - Mucheri, Vimbai (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScFoodSc)--Stellenbosch University, 2021.